DIGITAL TECHNOLOGIES IN DENTAL LABORATORY - Monica Tatarciuc; Anca Vițalariu; Diana Diaconu-Popa (Romanian Society of Oral Rehabilitation, 2021)
Digital CAD-CAM technologies are increasingly used in to the dental laboratory, for the realization of prosthetic appliances and for the realization of intermediate elements. Computerized methods, subtractive or additive, considerably reduce the number of clinical and technological steps, requires less materials, allow to obtain high-precision prostheses and reduce the risk of errors. This article aims to present the possibilities of ussing these techniques in to the dental technology and the methods applied to gain different prosthetic devices.